Enhancing Students’ Innovative Competence through Academic Creativity: An Analysis of The Role of Learning Innovation and Digital Literacy from The Perspective of Educational Management Based on the Componential Theory of Creativity - Arifannisa, Arifannisa; Shafiq, Muhammad Aqib; Harini, Hegar (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study investigates the role of learning innovation and digital literacy in enhancing students’ academic creativity and innovative competence in higher education, using Amabile’s Componential Theory of Creativity as the theoretical lens. A quantitative survey design was employed, using a Likert-scale questionnaire as the main research instrument to measure learning innovation, digital literacy, academic creativity, and innovative competence. Data were collected from 100 undergraduate students in Karawang, West Java Province, selected through purposive sampling based on their experience with project-based and technology-integrated learning. This sample size is considered adequate because it fulfills the minimum requirement for SEM-PLS analysis, which allows reliable estimation even with relatively small samples. Structural Equation Modeling using SmartPLS was applied to examine causal relationships among variables. The findings reveal that learning innovation significantly influences academic creativity, while digital literacy enhances innovative competence both directly and indirectly through academic creativity. Academic creativity is confirmed as a strong predictor of innovative competence, although it does not mediate the effect of learning innovation. These results underscore digital literacy as a foundational driver of creativity-based innovation, aligning with the needs of the digital era. The study contributes theoretically by extending the application of creativity theory within the Indonesian higher education context and provides practical implications for universities to strengthen digital-based innovative learning and curriculum development.